A comparative study between the effect s of Arctium lappa L. leaves extract and Pentoxifylline on DNA of sperms rats treated with Gentamicin - Alwan , Hassanin D.; Hasan , Huda F.; M-R Fakhirldin, Muhammad-Baqir (Iraqi Journal of Science, 2022)
This study were designed to make comparison between the influence alcoholic extract of Arctium lappa L. leaves and Pentoxifylline on treatment the adverse effect of gentamicin on DNA of sperms. Thirty five male rats were divided into 5 groups: the 1st group (T1) was made as negative control group, the 2nd group (T2) was given distilled water and gentamicin 5mg/kg (positive control group), the 3rd group (T3) was given a dose 600 mg/kg of Arctium lappa L and gentamicin, the 4th group (T4) was given dose 100mg/kg of pentoxifylline and gentamicin, the 5th group (T5) was given a dose 300mg/kg of Arctium lappa extract with dose 50mg/kg of pentoxifylline and gentamicin. The results of DNA damage% and agglutination % in T3, T4 and T5 appeared an important increase as compared with T2. Testosterone level in T3 and T5 showed an important arise when made comparison with T2 and T4. The section of testis in (T2) showed several destructions in the testis and sever necrosis of the seminiferous tubules, while the section of testis in (T3) showed slight odema in the interstitial tissues and decrease degenerative changes of the somniferous tubules. The section in (T4) showed odema in the interstitial tissues and blood vessels congestion, while the section in (T5) group showed development in tissue of testis, there is healthy spermatids and mild changes in the testis when compared with section of rat testis treated with pentoxifylline only. In this study concluded the Arctium lappa leaves extract and pentoxifylline have the ability to lessen the adverse action of gentamicin on DNA of sperms and Arctium lappa leaves caused improvement the action of pentoxifylline in improvement fertility.